Legal Entity Status of Individual Companies Which no Longer Meet the Criteria for Micro and Small Enterprises - Prasistanti, Aninda Rehani; Sihabudin, Sihabudin; Laila, Fathul (IJBLE Scientific Publications Community Inc., 2024)
An individual company is obliged to modify its legal status to a Capital Partnership Company if it is considered as no longer applies for Micro and Small Enterprises (UMK) / MSEs criteria. However, there are no provisions regarding the consequences if it is not made. It leads to unclear legal entity status and the responsibilities of individual companies which do not meet the standards of the Micro and Small Enterprises (UMK). This study aims to (1) analyze Individual Companies legal entity status which does not apply the UMK standards, and (2) analyze the legal implications of Individual Companies which no longer meet the UMK criteria. This study used normative juridical research method with a statutory approach and analysis of legal concepts. The results show that individual legal entity status of companies which do not meet the UMK criteria has not been rigidly regulated in the Job Creation Law or its regulations. However, individual companies which do not meet the UMK criteria are considered as no longer meet the legal entity requirements which are regulated in the Job Creation Law. Therefore, de jure, Individual Company legal entity status is no longer a legal entity, but de facto it is still registered as a legal entity. In addition, the legal implication is considered as the loss of the limited liability of the Individual Company.